2007
DOI: 10.1158/1535-7163.mct-07-0114
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans and their synthetic mimetics inhibit RANTES-induced migration and invasion of human hepatoma cells

Abstract: The CC-chemokine regulated on activation, normal T-cell expressed, and presumably secreted (RANTES)/CCL5 mediates its biological activities through activation of G protein -coupled receptors, CCR1, CCR3, or CCR5, and binds to glycosaminoglycans. This study was undertaken to investigate whether this chemokine is involved in hepatoma cell migration or invasion and to modulate these effects in vitro by the use of glycosaminoglycan mimetics. We show that the human hepatoma Huh7 and Hep3B cells express RANTES/CCL5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…Therefore, it is important to identify biological markers for extrahepatic metastasis in HCC so that preventive strategies such as adjuvant chemotherapy or targeted therapy can be initiated shortly after primary treatment. Several similar studies have shown that FAK plays as an important role in HCC progression, cancer invasion, and an independent prognostic factor for disease-free and overall survival [16][17][18]23] that was further confirmed in our study. However, our current study is the first to provide solid evidence that FAK overexpression in primary HCC predicts extrahepatic metastases in human subjects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, it is important to identify biological markers for extrahepatic metastasis in HCC so that preventive strategies such as adjuvant chemotherapy or targeted therapy can be initiated shortly after primary treatment. Several similar studies have shown that FAK plays as an important role in HCC progression, cancer invasion, and an independent prognostic factor for disease-free and overall survival [16][17][18]23] that was further confirmed in our study. However, our current study is the first to provide solid evidence that FAK overexpression in primary HCC predicts extrahepatic metastases in human subjects.…”
Section: Discussionsupporting
confidence: 89%
“…In HCC cell lines, FAK expression has long been correlated with invasiveness and aggressiveness [17][18][19]. Furthermore, FAK-mediated signals have not only been found to be involved in antiapoptotic effects [20] but are also correlated with several critical survival pathways such as cSrc [21] and PTEN [22].…”
Section: Introductionmentioning
confidence: 99%
“…The third group of inhibitors comprises GAG mimetics, which serve as 'decoys' of chemokines and bind to their receptors. Of these compounds, OTR4120 and OTR4131 inhibited CCL5-dependent migration and invasion of hepatoma cells in vitro (81). Consistent with this, in gastric cancer, Mencarelli et al (61) reported that inhibition of CCR5 signaling reduced gastric cancer cell migration and adhesion to explanted murine peritoneum in vitro.…”
Section: Therapeutic Implications Of C-c Motif Ccrs In Gastric Cancermentioning
confidence: 64%
“…Our results were consistent with those of other researches. Sutton et al found that the migration of hepatoma cells was inhibited when glycosaminoglycans and their synthetic mimetics, which could inhibit the combination of RANTES and CCR3/CCR5, were used [23] . Some scholars used siRNA to down-regulate the expression of CCR5 and the combination of RANTES and CCR5, and they found the metastatic ability of MDA-MB-231 breast cancer cells was also significantly suppressed [19] .…”
Section: Discussionmentioning
confidence: 99%